Creating accessible and inclusive undergraduate studentship opportunities: the ENRRICH experience - Robert Beattie; Kelly Russell; Kristy Wittmeier; Jenna Mitchell-Dueck; Kristene Cheung; Mojgan Rastegar; Alana Slike; Valerie Williams; Ming-Ka Chan; Mary Wilson; JLP Protudjer (BMC Medical Education)
Abstract Recognizing the systemic exclusion of structurally oppressed groups from academic awards, the ENRRICH (Excellence in Neurodevelopment and Rehabilitation Research In Child Health) summer studentship emphasized the inclusion of structurally oppressed groups. Herein, we outline the processes in creating this funding opportunity, and plans for improvement, including enhanced representation among supervisors.